Problematika Penerapan Kurikulum Merdeka Belajar di SD Negeri 060826 Kec. Medan Area - Herawati Herawati; Juni Mellyani Hasibuan; Rizka Fadhilah Priono; Zulhijjah Febriyani Sitepu (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
The implementation of teaching and learning activities in Indonesia is guided by the Curriculum. The curriculum is developed and refined in line with the rapid development of science and technology and the evolution of society. In the conditions of the COVID-19 pandemic, major changes have occurred in the world of education, especially in Indonesia, with a shift from direct learning in classrooms to distance education based on digital technology. The aim of this research is to analyze the effect of implementing the Independent Curriculum at SDN 060826 Kec. Medan Area. Through this approach, it is hoped to obtain a clearer picture of the effectiveness of the curriculum in improving the quality of education as well as identifying obstacles and opportunities that arise in its implementation. This research uses a descriptive qualitative method to analyze the effect of implementing the Merdeka Curriculum at SDN 060826 Kec. Medan Area. Research conducted by researchers at SDN 060826 Kec. Medan Area, it can be seen that they always regularly attend training from both the principal and teachers and to strengthen teachers' understanding of the Independent Learning Curriculum, teachers always hold monthly meetings with the Teacher Working Group (KKG) to resolve various problems related to the Independent Learning Curriculum. as well as to increase teacher competence in the process of teaching and learning activities.